Effects Of English Language Proficiency On Pragmatic Production And Comprehension Of Apology Amongst Jordanian Efl Learners - Al-Harbi, Hamzeh Mohammad (2020)
Researchers in the field of interlanguage pragmatic (ILP) development have shown a keen interest in investigating the factors that affect pragmatic competence. Language proficiency is one of the dominant independent factors in the field of ILP development (Taguchi, 2011; Xiao, 2015). In order to examine whether a relationship exists between language proficiency and pragmatic competence with regard to pragmatic production and comprehension, a mixed-method study was conducted on 300 Jordanian English as a foreign language (EFL) learners of Islamic Educational College (IEC) schools in Jordan and 100 native speakers of English (NSE). Based on Jordanian EFL learners’ scores in TOEFL Junior test, the 300 Jordanian learners were divided into three sub-groups: (1) beginner EFL learners (BEFLL), (2) intermediate EFL learners (IEFLL), and (3) advanced EFL learners (AEFLL), with 100 participants in each group. The conceptual framework of the study is based on Two-dimensional Model of Language Proficiency Development (Bialystok, 1993), Speech Act Theory (Searle, 1969), and Communicative Language Ability Model (Bachman & Palmer, 1996, 2010). Both quantitative and qualitative data were collected to answer the five research questions. While the quantitative data were collected using Written Discourse Completion Task (WDCT) and Multiple-Choice Discourse Completion Task (MDCT), the qualitative data were collected using semi-structured interviews.